Les activités, temps et lieux de vie des cadres - Laure Guilbert; Alain Lancry (Activités, 2005)
This research aims at understanding the management of activities, times and places of living by managers, in regards to their usage of technologies and methods of information and remote communication. We choose the theoretical perspective of the activity system, that considers that the different circles and times of socialisation of the individual constitute a system broken down into three sub-systems (professional, familial, personal and social) that are both autonomous and interdependent. Should one be modified, then all others are necessarily impacted. In this case, a new balance between the sub-systems has to be found. This model takes into account the active part of individuals, who try to conciliate their commitments in their different domains of life. We have constructed a longitudinal methodology which articulates self-observations and interviews guided by those self-observations. We have also used the ASI Protocol (Activity System Inventory) in order to access the relations that managers establish between their spheres of existence. Our methodological approach is therefore characterised by a triangulation of methods, which allows for a cross-fertilisation of data. The results confirm some suppositions regarding managers’ work and their important use of technologies and methods of information and remote communication. They also prove that the incursions between domains of life are reciprocal, and that technologies are only seldomly the vector of those incursions. Finally, bringing out the models of action and the models of life of managers allow to underline the active role of managers in their managing the organisation of their activities of life according to their constraints and their resources, personal, environmental and systemic.